2009
DOI: 10.1126/science.1168501
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Tegmental Area BDNF Induces an Opiate-Dependent–Like Reward State in Naïve Rats

Abstract: The neural mechanisms underlying the transition from a drug-nondependent to a drug-dependent state remain elusive. Chronic exposure to drugs has been shown to increase brain-derived neurotrophic factor (BDNF) levels in ventral tegmental area (VTA) neurons. BDNF infusions into the VTA potentiate several behavioral effects of drugs, including psychomotor sensitization and cue-induced drug seeking. We found that a single infusion of BDNF into the VTA promotes a shift from a dopamine-independent to a dopamine-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
153
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 22 publications
8
153
4
1
Order By: Relevance
“…Therefore, understanding the neurobiological substrates mediating the motivational properties of withdrawal from chronic nicotine is an important step in the development of new treatments for nicotine addiction. Previous reports have suggested that a neurobiological switch occurs during the transition from a drug-naive to a drug-dependent motivational state (32). The transition from acute nicotine use to nicotine dependence has been hypothesized to result from neuroadaptative changes that produce the powerful withdrawal syndrome and negative emotional state observed upon cessation of nicotine use (3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the neurobiological substrates mediating the motivational properties of withdrawal from chronic nicotine is an important step in the development of new treatments for nicotine addiction. Previous reports have suggested that a neurobiological switch occurs during the transition from a drug-naive to a drug-dependent motivational state (32). The transition from acute nicotine use to nicotine dependence has been hypothesized to result from neuroadaptative changes that produce the powerful withdrawal syndrome and negative emotional state observed upon cessation of nicotine use (3).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF expression facilitates opiate-associated neural plasticity 42 and the dopamine-dependent response to opiates. 6 Chronic exposure to opiates is associated with increased BDNF levels in the VTA 23 , and it has been demonstrated that this increase begins rapidly after initial usage. 43 Other studies have reported increased expression of BDNF in the VTA following morphine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1, IL-6 and TNF- have been shown to reduce morphine analgesia within five minutes of administration 4 , and blockade of IL-1 signalling prolongs morphine-induced analgesia 5 , thereby potentially implicating these three cytokines in morphine tolerance. Microglial activation is further implicated in the development of tolerance through increased expression of brain derived neurotrophic factor (BDNF) in the ventral tegmental area (VTA) that facilitates the switch to the dopaminedependent reward system present in addiction 6 . Notably, Bdnf -/-knockout mice do not develop tolerance to morphine 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological, molecular, and behavioral evidence supports the idea that a switch from an inhibitory to an excitatory VTA GABA A receptor does, in fact, occur in animals that have changed from a previously drug-naive motivational state, to an opiate-dependent and withdrawn state Vargas-Perez et al 2009). In previously drug-naive rats, the GABA A receptor agonist muscimol produced inhibition of GABA neurons via their direct actions on GABA A receptors .…”
Section: Vta Gaba a Receptors Form A Motivational Switching Mechanismmentioning
confidence: 79%
“…Similarly, it was proposed that the TPP-and dopamine-dependent reinforcement pathways observed by investigators might have their biological bases rooted in the biphasic actions of VTA GABA A receptors Vargas-Perez et al 2009). Such a model would require that opiates exert their actions (at least initially in drug-naive subjects) on the m-opioid receptors found presynaptically in the VTA, which regulate GABA release onto GABA A receptors (Fig.…”
Section: Vta Gaba a Receptors Form A Motivational Switching Mechanismmentioning
confidence: 99%